Kajian Terhadap Kualiti Penyelenggaran Jalan Persekutuan di Johor Bahru: Dari Perspektif Pengguna - Shafii, Haryati; Abd Halid @ Mohd Halid, Muhammad Aliff Haiqal; Mat Yassin, Azlina; Masram, Haidaliza; Sarpin, Norliana (Research in Management of Technology and Business, 2021)
Road Maintenance is an important aspect to ensure the quality of roads is always in good condition. The problem of this study is the issue of poor road maintenance which has led to an increase in accident cases among users. This study aims to examine users' perceptions of the quality of Federal Road maintenance, identify the factors that cause damage to the quality of Federal Roads and describe the safety factors during Federal Road maintenance. This study focuses on users who pass through the Federal Road to the city center. The study location is at KM 12.7 Johor Bahru-Skudai which has a high traffic rate during peak hours because this route is the main link road. This study uses a quantitative approach using a questionnaire study instrument. A total of 94 respondents were involved in this study. The results of the study revealed that the majority of users' perceptions of the quality of Federal Road maintenance are not good which can contribute to road accidents. The main factor causing road damage is that trucks carrying excessive loads have caused road damage. Federal Road Maintenance requires improvements to the procedures used, especially involving road paving works. In conclusion, the quality of Federal road maintenance in terms of quality, is very important to ensure the safety of users.